2013
DOI: 10.1371/journal.pone.0071547
|View full text |Cite
|
Sign up to set email alerts
|

A Chemically Defined Medium for Rabbit Embryo Cryopreservation

Abstract: This study evaluates a new synthetic substitute (CRYO3, Ref. 5617, Stem Alpha, France) for animal-based products in rabbit embryo cryopreservation solutions. This evaluation was performed using two approaches: a thermodynamic approach using differential scanning calorimetry and a biological approach using rabbit embryo slow-freezing. During the experiment, foetal calf serum (FCS) was used as a reference. Because FCS varies widely by supplier, three different FCS were selected for the thermodynamic approach. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
(58 reference statements)
1
7
0
1
Order By: Relevance
“…This synthetic medium induced acceptable viability rates, growth recoveries and pluripotency gene expression when supplemented with 4–5% cryoprotectant. These data are consistent with our previous studies on embryo cryopreservation [ 38 , 39 , 44 ] and with other studies which showed that FBS could be replaced by a commercial synthetic media containing a high molecular weight polymer when freezing human or mouse PSCs [ 52 , 53 , 54 , 55 ]. In our study, we compared CRYO3, a synthetic commercial product accredited for clinical purposes, with CryoStor ® CS10, a widely used stem cell freezing medium of unknown composition.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This synthetic medium induced acceptable viability rates, growth recoveries and pluripotency gene expression when supplemented with 4–5% cryoprotectant. These data are consistent with our previous studies on embryo cryopreservation [ 38 , 39 , 44 ] and with other studies which showed that FBS could be replaced by a commercial synthetic media containing a high molecular weight polymer when freezing human or mouse PSCs [ 52 , 53 , 54 , 55 ]. In our study, we compared CRYO3, a synthetic commercial product accredited for clinical purposes, with CryoStor ® CS10, a widely used stem cell freezing medium of unknown composition.…”
Section: Discussionsupporting
confidence: 93%
“…We further observed that the CRYO3-based medium exhibited a more variable ∆H than CryoStor ® CS10, suggesting that the former was less thermodynamically stable. However, this instability of CRYO3 was not previously observed in studies of embryo freezing media [ 38 , 44 ]. Except for CryoStor ® CS10, all freezing media exhibited similar thermodynamic patterns that corresponded to reduced viability in the thawed cells.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Існують роботи, в яких 6-7% ГЕК розглянуто як замінник протеїнів сироватки крові для кріоконсервування еритроцитів [28,29]. Нами також використаний цей підхід при обранні концентрацій полімерних сполук -ПЕО та ГЕК, які потенційно можуть заміщувати дію протеїнів сироватки під час кріоконсервування [30], але ПЕО за даних концентрацій виявився неефективним.…”
Section: загальна збереженість (25%~75%)unclassified
“…Although a great deal of effort has been expended in improving cell cryopreservation [1,2], a considerable amount of specially designed cryopreservation solution [3][4][5][6][7] is still required and low cell viability at the time of thawing remains a serious problem. Accordingly, availing of the newly developed high-speed vitrification cryopreservation system, we propose an ultra-high heat flux vitrification (quenching) method that uses a micro-nano fine solid nitrogen (SN 2 ) particulate spray [8,9].…”
Section: Introductionmentioning
confidence: 99%